TERAPI SENI BERBANTUAN KARAWITAN UNTUK MENINGKATKAN AKTUALISASI ESTETIS BAGI DISABILITAS SENSORIK NETRA DI PPSDN PENDOWO KABUPATEN KUDUS - Fathurohman, Irfai; Wasis Wijayanto; Sugoro Bhakti Sutono; Sri Surachmi W; Ahmad Hariyadi; Nur Fajrie; Sa'aduddin Annasih (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This art therapy assisted by gamelan is an art group of Terasku ( Art Therapy Kudus) from Muria Kudus University. Community service activities are carried out by this Terasku art group at the Pendowo visual sensory disability social service center (PPSDSN) in Kudus Regency by providing art therapy assisted by gamelan to improve aesthetic actualization for beneficiaries (PM), namely visual sensory disabilities at the Pendowo blind sensory disability social service center in Kudus Regency. Aesthetic actualization is carried out assisted by gamelan as a medium to develop aesthetic potential and cultural identity, while facing challenges that arise due to sensory limitations. The objectives of this community service activity are (1) to improve the quality of life for visual sensory disabilities, (2) to provide space for self-actualization and development of aesthetic potential, (3) to preserve local arts and culture, (4) to improve social inclusion and equality through gamelan art for visual sensory disabilities, (5) to develop social and interpersonal skills, (6) to empower and be independent through gamelan art for visual sensory disabilities. This community service activity has been carried out at PPSDN Pendowo Kudus Regency from August to November 2024. Based on the results of the activities that have been carried out, it shows that visual sensory disabilities have been able to present karawitan art performances and have applied karawitan art skills well for aesthetic actualization.